PROFIL SEORANG DOSEN TUNANETRA DI INSTITUT SENI INDONESIA PADANG PANJANG - Marlina - Lisa (Universitas Negeri Padang, 2012)
This research was the discovery of a blind Professor begins the initials he has talent special in the field of music. See it then it can be formulated in this research issue i.e. How does the blind Professor profile at Art Institute Indonesia Padang Panjang. This research uses descriptive qualitative approach to look at the profile of a college professor who are blind. The subject is a college professor who are blind. The collection of data in this study through observation, interviews, and documentation.From the results of the research appear that the birth of a history lecturer blind to walk normally. He was the third child of six siblings and married in 1967 but he did not have children. As for the causes of blindness, known since he was a toddler and grow just like the other kids. Because it has a strong desire to learn the violin, then he was sent to study abroad (Belgium). After completing his studies abroad and won, then he returned to Indonesia and served as educators (Lecturer) at the Art Institute Indonesia Padang Panjang.